(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article presents strategies for teaching neologisms to ESP students specializing in economics. It focuses on the challenges students face when encountering newly created words and the need to interpret these expressions accurately. The study aims to develop, justify, and propose practical tasks based on authentic language materials to enhance students’ learning skills in understanding and translating neologisms. The findings demonstrate the effectiveness of the suggested action plan, which is designed specifically for ESP students in higher education.